Optical study on intrinsic exciton states in high-quality CH3NH3PbBr3 single crystals - Thu Ha Do, T. (2018)
Organolead halide perovskites have emerged as potential building blocks for photovoltaic and optoelectronic devices. Yet the underlying fundamental physics is not well understood. There is lack of agreement on the electronic band structures and binding energies of coupled electron-hole pairs (excitons), which drive the photophysical processes. In this work, we conducted temperature-dependent reflectance and photoluminescence experiments on high-quality CH3NH3PbBr3 single crystals. Two direct optical transitions corresponding to intrinsic free-excitons are clearly resolved, showing excellent consistence between the low-temperature (T=10 K) reflectance and photoluminescence spectra. Remarkably, the excitons have different binding energies and behave oppositely with temperature, suggesting distinctive origins. Moreover, the asymmetric photoluminescence profile is counterintuitively dominated by the high-energy exciton that is explained by a long relaxation time between levels and by the favorable generation rate of electron-hole pairs at the high-energy band. Our study opens access to the intrinsic properties of CH3NH3PbBr3 and sheds light to reconcile the large range of binding energies reported on these emergent direct band-gap semiconductors.